Contemporary Roles of Librarians in Navigating and Addressing Academic Research Ethical Dilemmas: The Technical Universities in Perspective - Barfi, Faustina Kyerewaa; Alemna, Anaba A.; Adjei, Emmanuel; Brew, Edwin Mends (Consortium of Academic and Research Libraries in Ghana, 2018)
The polytechnics in Ghana are currently been upgraded to Technical University status. In view of this, academic research and, for that matter, compliance to research ethics has become imperative in these institutions notwithstanding concerns on ranking, funding, open scholarship, virtual research, and reputation building have also come into play. Academic writing is guided by laid down rules, standards and codes of conduct in order to uphold intellectual integrity and honesty. As such, behavioural attitudes, the ‘‘duty-based theory which complements the need for compliance to academic research policies, rules and codes of conducts has been espoused. The researchers explored the librarians’ role in support of the Technical University new road map. This is an exploratory study that adopted the quantitative method. Senior Polytechnic Librarians whose institutions had undergone the transition became the resultant respondents. A questionnaire was the instrument used for the data collection. Twenty-six responses were analysed using SPSS to ascertain the results Findings revealed a number of roles deemed traditional and contemporary. Although the librarians play crucial roles by instilling academic discipline, emerging roles and use of Information Communication Technology (ICT) applications were minimal. The study revealed plagiarism, fabrication, poor record keeping, honorary authorship, conflict of interest, duplication particularly of dissertations as some of the dilemmas of scholarly communication. Other delinquencies were data insecurity, social network abuse and issues on e-waste. It was discovered that integration of ICT has impacted on academic research and for that matter on ethics. The benefits of adhering to ethical standards promote integrity in research, impact on institution’s reputation, ranking, funding, transparency amongst others. Innovative applications, interactive and collaborative approaches, policy and compliance, sensitisation and education amongst others were recommended as remedies to manage and curtail the menace of violations of research ethics. The study ascertained the degree of awareness of these dilemmas among the librarians. It postulated vigorous ethical scrutiny and research enquiry to ensure that research findings improve human conditions both present and future. As Librarians our traditional roles are currently embedded with the new and challenging tasks.
Research Article
Keywords: Research Ethics, Ethical Dilemmas, Technical Universities, Intellectual Honesty